PENERAPAN METODE AGILE DALAM MANAJEMEN PROYEK: SYSTEMATIC LITERATURE REVIEW - Hidayah, Nur Aeni; Nur Muhammad Asnadi (JURNAL PERANGKAT LUNAK, 2024)
Rapid developments in the business world encourage organizations to be more adaptive and responsive in the face of challenges. To create new products and stay competitive with competitors, organizations need to plan carefully. Efficient project management and optimal use of resources are key to success in this regard. The Agile method has been recognized as an approach that can meet the needs of organizations in the face of rapid change. Therefore, this research will use the Systematic Literature Review (SLR) method to review and summarize previous studies related to the application of Agile methods in project management. After conducting a search with several conditions, the researcher collected journal articles, as many as 16 relevant journal articles were collected for review. The results of the study show that the application of Agile methods helps significantly in project management.